1. Distribute the -5 on the right side of the equation: 4 - 2x = -5x - 35
2. Add 5x to both sides to isolate x: 4 - 2x + 5x = -5x + 5x - 35
3. Simplify the left side to 3x: 4 + 3x = -35
4. Subtract 4 from both sides: 4 + 3x - 4 = -35 - 4
5. Simplify to get 3x = -39
6. Divide by 3 to solve for x: 3x / 3 = -39 / 3
7. Simplify to find x = -13
4−2x=−5(x+7)
(order the steps)
8 of 158 of 15 Items
Question
Put the steps of solving the equation for x
in order from the first step through finding the value of x
.
4−2x=−5(x+7)
3x = -39
3x/3 = -39/3
4 - 4 + 3x= -35 - 4
4 + 3x= -35
4 - 2x + 5x= -5x + 5x - 35
x= -13
1 answer